The Categorical Imperative in Defence of Animal Rights. Christine Korsgaard’s Ethical Extensionism - Adamska, Małgorzata (ETHICS IN PROGRESS, 2018)
In this paper, I present Christine Korsgaard’s style of building a conception of animal rights protection based on a concept of Kantian provenance, namely “end in itself”. Considering that an end in itself in Immanuel Kant’s philosophy includes only human beings, the American philosopher needed to modify (extend) the meaning of the abovementioned concept. This study aims at showing this change of the meaning in categories derived from Fregean semantics (sense and reference). Moreover, I will attempt to prove that by broadening the extension of “end in itself” Korsgaard uses a strategy called ethical extensionism and situates the revised (naturalized) categorical imperative ipso facto within environmental ethics. I start with elucidating Korsgaard’s views on the meaning of “end in itself” before she took interest in animal rights (set out mainly in Kant’s Formula of Humanity and The Sources of Normativity) and then I synthetically describe her animal rights philosophy with a special regard to the category of “natural good”. The second part of the article explains the methodology used in the paper, while the last part is intended to be an interpretation of Korsgaard’s thought.